Obraz Turka osmańskiego — między mitem, historią a przekładem (na marginesie dwóch powieści historycznych Wery Mutafczijewej) - Kovacheva, Adriana (Przekłady Literatur Słowiańskich, 2011)
Representations of Ottoman Turks — between myth, history and translation (about two historical novels of Vera Mutafchieva) This paper raises two main questions. The first one is how to situate the strategy of representation of Ottoman Turks in historical novels of Vera Mutafchieva The Djem Affair and The Last Shishmans in the frames of bulgarian historical and literary context of the ‘60s and ‘70s of the 20th century. It is not possibile to describe this strategy without reference to the impact of folklore and nineteenth century tradition of representing the Muslims and Turks. In this context fields three themes that causes conflicts are distinguished and their interpretation in the translation of the novel could be used as a criterium for the translation’s evaluation. These themes are the notion of East and West, the topic of multiethnicity in Ottoman Empire and bulgarian stereotypes of Turks, Islam and national identity. The second question is how the Polish translator interpreted above mentioned historical novels of Mutafchieva. The analysis of some important details shows that the polish translation of The Djem Affair do not follow original emphases and thus eliminate some local meanings of the novel, which means that it obliterates some of its key conflicts and contradictions.